2015
DOI: 10.1007/s13300-015-0100-8
|View full text |Cite|
|
Sign up to set email alerts
|

Starting Insulin in Type 2 Diabetes: Real-World Outcomes After the First 12 Months of Insulin Therapy in a New Zealand Cohort

Abstract: AimsCurrently, there is no consensus on which form of insulin to use when initiating insulin in type 2 diabetes (T2D). Our aim was to compare glycated hemoglobin (HbA1C) reduction, weight change and severe hypoglycemia rates during the first year after initiation of intermediate-acting insulin isophane, insulin glargine and pre-mixed insulin in patients with T2D.MethodsElectronic clinical records of patients with T2D, starting insulin at a tertiary referral center in Auckland, New Zealand, from January 1 to De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…57 Ideally, these discussions would Studies indicate that once treatment with basal insulin has been initiated, glycaemic control is still not achieved in the majority of cases 78,79 and that this is partly attributable to insufficient titration of insulin. 33,44 A study by Blak et al, 78 Germany, 80 New Zealand 81 and China. 82 This is in contrast to data from the plethora of clinical trials 74,75 that entail close monitoring by trial staff of motivated participants following strict titration algorithms.…”
Section: Methods To Tackle Initiation Inertiamentioning
confidence: 99%
See 3 more Smart Citations
“…57 Ideally, these discussions would Studies indicate that once treatment with basal insulin has been initiated, glycaemic control is still not achieved in the majority of cases 78,79 and that this is partly attributable to insufficient titration of insulin. 33,44 A study by Blak et al, 78 Germany, 80 New Zealand 81 and China. 82 This is in contrast to data from the plethora of clinical trials 74,75 that entail close monitoring by trial staff of motivated participants following strict titration algorithms.…”
Section: Methods To Tackle Initiation Inertiamentioning
confidence: 99%
“…A study by Blak et al, in 2012, revealed that only 17.3% of participants achieved HbA1c <7% (53 mmol/mol) after a mean follow‐up of 2.9 years, while 141 (41%) participants in a study by Dale et al, in 2010, achieved the pre‐2006/2007 UK Quality and Outcomes Framework target of ≤7.4% (57 mmol/mol) after 36 months of basal insulin therapy. In addition, modest titration of basal insulin in a real‐world setting has been observed in studies from Germany, New Zealand and China . This is in contrast to data from the plethora of clinical trials that entail close monitoring by trial staff of motivated participants following strict titration algorithms .…”
Section: Inertia With Regard To Insulin Titrationmentioning
confidence: 97%
See 2 more Smart Citations
“…ORBIT was the largest observational study of basal insulin utility in China, which showed that the dose of basal insulin among patients with uncontrolled T2D increased by only 0.034 U/kg/d during 6 months after treatment initiation, with a mean starting dose of 0.18 ± 0.07 U/kg/d . Observational studies from other countries have also reported that, 1 year after treatment initiation, basal insulin only increased by 0.1 U/kg/d.…”
Section: Introductionmentioning
confidence: 99%